Economics for business - Mulhearn, Chris; Vane, Howard R.; Eden, James (New York : Palgrave Macmillan, 2015)
"A concise and vibrant introduction to economics for business and management students which covers all the most relevant theory applied to engaging examples from the business world and everyday life, offering insights from real-life managers into their use of economics at work"--
Machine generated contents note: -- 1. Economics and business -- 2. The market -- 3. The firm -- 4. Firms' costs and revenues -- 5. Market concentration and power -- 6.Investment Policy and Appraisal 7. Business and government -- 8. Factor markets -- 9. The macroeconomy, macroeconomic policy and business -- 10. Unemployment and Inflation -- 11. Economic growth and business cycles -- 12. Stabilizing the economy -- 13. International trade -- 14. The balance of payments and exchange rates -- 15. Multinational Firms -- 16.International or Global Economy?
Includes index.
Keywords: Economics; Business; Commerce; Managerial economics; BUSINESS & ECONOMICS / Economics / General